Enhanced Purkinje cell survival but compromised cerebellar function in targeted anti-apoptotic protein transgenic mice - Goswami, Jaideep; Martin, Loren A.; Goldowitz, Daniel; Beitz, Alvin J.; Feddersen, Rod M. (Molecular and cellular neuroscience, 2005)
Regulation of Purkinje cell (PC) number is critical for proper assembly and function of the cerebellum. Murine cerebellar neurogenesis yields supernumerary populations of cells that are subject to programmed cell death during development and aging. This study focuses on the control of mouse PC number during development and the consequences of interrupting normal cell death. Purkinje cell-specific regulatory elements from the pcp2 gene were employed to target expression of two anti-apoptotic proteins, human BCL-2 and adenovirus E1B 19k to the PCs of transgenic mice. Comparative morphometric analyses indicated no significant difference in PC numbers in the strongest BCL-2 expressing line, while a 14.2% increase was noted in the pcp2/E1B 19k transgenic line. The temporal transgene expression patterns of several mouse lines indicated that PC numbers are normally adjusted during the first postnatal week. Crossbreeding studies demonstrated that both Bcl-2 and E1B 19k transgenes provided Purkinje cell protection from SV40 Tag-induced cell death. Interestingly, RotaRod behavioral analysis demonstrated that ‘rescued’ Purkinje cells degrade cerebellar function. Furthermore, aged E1B 19k and Bcl-2 mice exhibited decreased RotaRod performance despite increased PC numbers. These findings have implications regarding neuronal death during development and aging as well as cellular and genetic strategies to circumvent neuronal degeneration.